Comparison Between Gemcitabine-Cisplatin Chemotherapy Outcome and Body Mass Index in Muscle Invasive Bladder Cancer Patients At Dr. Saiful Anwar General Hospital Malang, Indonesia - Kurnia Penta Seputra; Besut Daryanto; Astarin Ardiani (Brawijaya Journal of Urology, 2020)
Introduction: Malignancy remain a worldwide challenge to overcome, one of the most common malignancy in men is bladder cancer, it represent the seventh most common cause of cancer in men worldwide. Over the past decade 6978 Indonesian were diagnosed with bladder cancer. In Dr. Saiful Anwar Hospital itself, 287 inpatient were hospitalized due to bladder cancer over the past 5 years. Bladder cancer therapy including, radical cystectomy, radiotherapy and chemotherapy depending on the tumor’s stage. Patients requiring chemotherapy, are given six course of Gemcitabine-Cisplatin regiment. Body Mass Index (BMI) acclaimed to take part in cancer treatment outcome, therefore this study aimed to compared body mass index with bladder tumor outcome in bladder cancer patients receiving six course of Gemcitabine-Cisplatin chemotherapy. Method: Fifteen bladder cancer patients with different BMI underwent (transurethral resection of bladder tumor) TURBT staging and received six course of Gemcitabine-Cisplatin Chemotherapy from 2016 to 2018 at Dr. Saiful Anwar General Hospital were recorded, we followed the patients during the six course of chemotherapy and evaluation were carried out using cystoscopy and bladder biopsy. The data then analysed using chi square and t-test to compared. Result: Fifteen patients were eligible for this study, 10 were men and 5 were women. Mean age is 66.6 years old, body mass index (BMI) include normal weight (73.3%), underweight (6.67%), overweight(13.3%) and obese (6.67%). Pathology finding including Transitional Cell Carcinoma of high grade (46,7%) and low grade (53.3%). Tumor staging start from T2 (26.67%), T3 (6.67%) and T4 (66.66%). Three patients had metastatic tumor to the liver, liver and lung and rectum respectively. Lymph node involvement were N0 40%(6),N1 33.3% (5) N2 20%(3) and N3 6.7% (1) continuously. Out of fifteen patients who underwent Gemcitabine-Cisplatin chemotherapy for six series, tumor outcome after therapy was compared with the BMI. Tumor still remain in 11 patient (73.3%), while 4 (26.7%) patients were found to be tumor free after six course of Gemcitabine-Cisplatin chemotherapy. There is no statistically significant between body mass index and chemotherapy success rate (p= 0.159) in this study. Although. there were statistically significant found in the presence of tumor before and after Gemcitabine-Cisplatin chemotherapy (p= 0.041). There are no statistically significant between sex and age when compared to chemotherapy outcome with (p=0.446) and (p=0.469) respectively. Conclusion: Body Mass Index has no relation in determining success rate of bladder cancer chemotherapy using Gemcitabine-Cisplatin.